AUSTENITIC TYPE STAINLESS STEEL PRODUCTION BY FOUNDRY - Nurdin Effendi (Urania : Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2010)
ABSTRACT Austenitic Type Stainless Steel Production by Foundry. Synthesis of austenite stainless steel using extracted minerals from Indonesian mines has been carried out. The starting materials for  austenite alloy consist of granular ferro-scrap, nickel, ferro-chrome, ferro-manganese, and ferro-silicon. A small quantity of  titanium has been added to it, and an extremely low carbon content is maintained in the alloy. However before the actual alloying work starts, the first important step is to carry out the determination of the fractional amount of each starting material necessary to form an austenite stainless steel alloy as specified. Once the componential fraction of each base alloy-element is determined, the raw materials are weighed on the microbalance. After the fractional quantities of each constituent have been computed, an appropriate amount of these base materials are weighed separately on the microscale.  The raw materials are then placed in the induction foundry furnace, which is operated by an electromagnetic inductive-thermal system. The foundry furnace system performs the stirring of the molten materials automatically. The homogenized molten metals are poured down into sand casting prepared in advance. Some of the austenite stainless steel was given heat treatment, followed by preliminary characterization. The microstructure observation concludes that an extensive portion of the sample’s surface turns out to be homogenous and that the grain boundaries appear to be well-defined. X-ray diffraction analysis shows that the material belongs to the fcc crystallographic system, which fits in with the austenite class of the alloy. The Vickers scale hardness distribution in the prehomogenized austenite stainless steel is relative high. The experimental fractional elemental composition data acquired by OES method turn out to differ slightly from the theoretical assumption. Keywords: Stainless Steel, Austenite, synthesis, mining materials.   ABSTRAK: Pembuatan Baja Tahan Karat Jenis Austenit Dengan Pengecoran. Telah dibuat baja austenitik tahan karat dari bahan-bahan tambang yang digali di Indonesia; Bahan-bahan tambang tersebut berupa ferro scrap, ferro chrome, ferro mangan, ferro silicon dan ferro nikel yang kesemuanya dalam bentuk granular-granular.  Austenitic yang dibuat ini juga diberi sedikit titan, serta memiliki kandungan karbon yang sangat rendah. Pembuatan dimulai dengan menghitung porsi bahan-bahan tersebut dari data-data spesifikasi yang diberikan, agar spesifikasi komposisi feritik yang dibuat sesuai dengan yang dikehendaki.  Setelah kuantitas dari setiap bahan mentahnya ditemukan, maka dilakukan penimbangan. Pekerjaan dilanjutkan dengan memasukkan bahan-bahan tersebut kedalam foundry furnace induksi yang memiliki sistem pemanasan induksi elektromagnet. Setelah bahan-bahan tersebut mencair, maka pengadukan dilakukan secara otomatis dari sistem foundry furnace tersebut. Kemudian cairan baja yang telah homogen tersebut dituang kedalam cetakan pasir. Pada sebagian baja tahan karat austenitik tersebut diberi perlakukan panas, dan dilakukan karakterisasi awal. Pengamatan struktur mikro menunjukkan bahwa bahan relatif homogen secara luas dan batas butirnya terlihat jelas.  Pola difraksinya menunjukkan bahwa bahan memiliki struktur kristal fcc yang sesuai dengan baja jenis austenitik Distribusi kekerasan dalam skala Vickers ingot sebelum homogenisasi relatif tinggi. Pengamatan distribusi unsur dilakukan dengan alat optical emision spectrometry (OES) dan hasilnya agak berbeda dengan design spesifikasi yang dikehendaki. Kata kunci: Baja Tahan Karat, Austenit, pembuatan, pengecoran